Training used in the Professional Development of Nepali Language Teachers - Bhandari , Dwarika Prasad (Orchid Academia Siraha, 2024)
This article explores the role of trainings in the professional development of Nepali language teachers. The study is grounded in a qualitative research framework and highlights the significance of training in enhancing teachers’ professional growth. Professional training is regarded as a key mechanism for keeping teachers updated, committed to their profession, effective in their practice, and focused on achieving results. In addition to formal training, the knowledge, skills, and experiences teachers acquire through classroom practice also contribute meaningfully to their professional development.The research incorporates both library-based study and field research methods, utilizing records of various training programs and employing descriptive as well as analytical approaches. Teacher training is recognized as an effective tool for promoting professional growth.The study identifies several forms of professional training designed specifically for Nepali language teachers. Among these, Teacher Professional Development (TPD) programs, action research, the formation of learning communities, team teaching, and distance education are regarded as particularly impactful. The study shows that when these trainings are implemented effectively, it significantly enhances the professional capabilities of Nepali language teachers.